HAMAS CHARTER: CHANGES AND PRINCIPLES - Adwan, Issam M. A. (Politikologija religije, 2019)
The paper examines the differences between the old charter of the Islamic Resistance Movement “Hamas” in 1988 and its political declaration document issued in 2017, titled “Principles and General Policies”. Which redefined the movement and its objectives and vision in concern of Palestine and its main issues, such as Jerusalem and the refugees. In addition, the charter redefined the main regional and international dimensions of the Palestinian cause and the movement’s view of Zionism and Israel, and its position on the Palestine Liberation organization “PLO.” The study was based on in-depth analysis of Hamas-relateddocuments and primary sources. The study is concluded with significant results that signify and highlight some important variables and changes in Hamas’ moderated charter; including, but not limited to, the changes of its objectives, and the use of modern language, best found in the movement redefining itself as aliberation movement.